2001
DOI: 10.1071/pp00096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth substances on the protoplasmic drought tolerance of leaf cells of the resurrection grass, Sporobolus stapfianus

Abstract: Hydrated leaves of the resurrection grass Sporobolus stapfianus Gandoger are not desiccation tolerant, but moderate to severe drought stress can induce their desiccation tolerance while the leaves remain attached to drying intact plants. Free-cell suspensions prepared from fully turgid leaves of S. stapfianus were also found to be desiccation-sensitive. In this study a sensitive assay was developed to determine the effect of exogenous substances on the protoplasmic drought tolerance (PDT) of cell suspensions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…1 The resurrection grass S. stapfianus Gandoger in the hydrated and desiccated state, respectively drought tolerance of S. stapfianus mesophyll cells, methyl jasmonic acid was the most effective. However, the increment of 6 MPa is well below the 500 MPa increase in protoplasmic drought tolerance induced in intact S. stapfianus plants by drought (Ghasempour et al 2001). Nevertheless, several S. stapfianus genes thought to be associated with desiccation tolerance (Neale et al 2000;Le et al 2007) are induced by methyl jasmonate (unpublished result) further supporting a role for methyl jasmonate in desiccation tolerance in S. stapfianus.…”
Section: Resurrection Plants and The Evolution Of Desiccation-tolerancementioning
confidence: 63%
“…1 The resurrection grass S. stapfianus Gandoger in the hydrated and desiccated state, respectively drought tolerance of S. stapfianus mesophyll cells, methyl jasmonic acid was the most effective. However, the increment of 6 MPa is well below the 500 MPa increase in protoplasmic drought tolerance induced in intact S. stapfianus plants by drought (Ghasempour et al 2001). Nevertheless, several S. stapfianus genes thought to be associated with desiccation tolerance (Neale et al 2000;Le et al 2007) are induced by methyl jasmonate (unpublished result) further supporting a role for methyl jasmonate in desiccation tolerance in S. stapfianus.…”
Section: Resurrection Plants and The Evolution Of Desiccation-tolerancementioning
confidence: 63%
“…During this period there was a period of desiccation, seed water contents returning to initial values. Although one may speculate that SA increases were induced to withstand desiccation due to the involvement of this compound in desiccation tolerance (Ghasempour et al, 2001;Senaratna et al, 2000), it is very difficult to certainly know this, since SA levels were low in non-buried (desiccated) seeds and ABA -which is also involved in conferring desiccation tolerance (Finkelstein et al, 2008) -did not follow the same trend compared to SA. Another factor leading to a rise in endogenous SA concentrations might be a defensive response against fungal and bacterial pathogens (Martínez et al, 2004;Mur et al, 2000), an aspect that warrants further research.…”
Section: Discussionmentioning
confidence: 90%
“…Brassinosteroids, methyl jasmonate, and ethylene promoted PDT in S. stapfianus to a higher degree than ABA, but not to a sufficient level to allow the plant to survive desiccation. Of the hormones normally associated with cell differentiation and growth, auxins had no effect, while cytokinins had a deleterious effect on PDT (Ghasempour et al 2001).…”
Section: Effects Of Hormones On Desiccation Tolerancementioning
confidence: 97%
“…In S. stapfianus, ABA level increases 6-fold during strong drought stress, and reaches a maximum during severe desiccation (20-10% relative water content). However, studies with S. stapfianus protoplasts showed that exogenously applied ABA only promotes protoplasmic drought tolerance (PDT) to a degree that is very much less than is required for desiccation tolerance (Ghasempour et al 2001). Brassinosteroids, methyl jasmonate, and ethylene promoted PDT in S. stapfianus to a higher degree than ABA, but not to a sufficient level to allow the plant to survive desiccation.…”
Section: Effects Of Hormones On Desiccation Tolerancementioning
confidence: 99%